Building public trust in COVID-19 vaccines through the Catholic Church in the Philippines - Gopez, Jose Ma W (J Public Health (Oxf), 2021)
Due to the expedited production of the COVID-19 vaccines and other issues related to it, many Filipinos are hesitant to receive the inoculation program set by the government. Because of this, it is crucial to gain public trust for the COVID-19 vaccines. This paper argues that the Catholic Church, being an influential institution in the Philippines, can help in building public trust in COVID-19 vaccines in the country.